Radio jet structures at ∼100 pc and larger scales of the γ-ray-emitting narrow-line Seyfert 1 galaxy PMN J0948+0022. Issue 1 (11th May 2019) - Doi, Akihiro; Nakahara, Satomi; Nakamura, Masanori; Kino, Motoki; Kawakatu, Nozomu; Nagai, Hiroshi
Abstract: The narrow-line Seyfert 1 (NLS1) galaxy PMN J0948+0022 is an archetype of γ-ray-emitting NLS1s in active galactic nuclei (AGNs). In this study, we investigate its radio structures using archival data obtained using the Karl G. Jansky Very Large Array (VLA) and the Very Long Baseline Array (VLBA). The new VLA images reveal an outermost radio emission separated by 9.1 arcsec. Its resolved structure and steep spectrum suggest a terminal shock in a radio lobe energized by the jet from the PMN J0948+0022 nucleus. This large-scale radio component is found at almost the same position angle as that of the pc-scale jet, indicating a stable jet direction up to ∼1 Mpc. Its apparent one-sidedness implies a moderate advancing speed (β > 0.27). The kinematic age of <1× 10 7 yr of the jet activity is consistent with the expected NLS1 phase of ∼10 7 yr in the AGN lifetime. The VLBA image reveals the jet structure at distances ranging from r = 0.82 milliarcsec to 3.5 milliarcsec, corresponding to approximately 100 pc, where superluminal motions were found. The jet width profile (∝ r 1.12 ) and flux-density profile (∝ r −1.44 ) depending on the distance r along the jet suggest that the jet kinetic energy is converted to internal energy in this region. The jet is causally connected in a nearly conical streamline, which is supported by ambient pressure at 100 pc scales in the host galaxy of PMN J0948+0022.